Disparities in Breast Cancer Incidence, Mortality, and Quality of Care among African American and European American Women in South Carolina. Issue 1 (January 2016) - Samson, Marsha E.; Porter, Nancy G.; Hurley, Deborah M.; Adams, Swann A.; Eberth, Jan M.
Abstract : Objectives: Breast cancer is the most frequently diagnosed cancer among women and the second-leading cause of female cancer deaths in the United States. African Americans and other minorities in the United States experience lower survival rates and have a worse prognosis than European Americans despite European Americans having a much higher incidence of the disease. Adherence to breast cancer treatment–quality measures is limited, particularly when the data are stratified by race/ethnicity. Methods: We aimed to examine breast cancer incidence and mortality trends in South Carolina by race and explore possible racial disparities in the quality of breast cancer treatment received in South Carolina. Results: African Americans have high rates of mammography and clinical breast examination screenings yet suffer lower survival compared with European Americans. For most treatment-quality metrics, South Carolina fairs well in comparison to the United States as a whole; however, South Carolina hospitals overall lag behind South Carolina Commission on Cancer–accredited hospitals for all measured quality indicators, including needle biopsy utilization, breast-conserving surgeries, and timely use of radiation therapy. Accreditation may a play a major role in increasing the standard of care related to breast cancer diagnosis and treatment. Conclusions: These descriptive findings may provide significant insight for future interventions and policies aimed at eliminating racial/ethnic disparities in health outcomes. Further risk-reduction approaches are necessary to reduce minority group mortality rates, especially among African American women. Abstract : This article examines breast cancer incidence and mortality trends in South Carolina by race and explores racial disparities in the quality of breast cancer treatment received in South Carolina compared with the United States as a whole. It also provides a basis to improve cancer care.